2001
DOI: 10.3171/foc.2001.10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal neurenteric cysts and their relation to more common aspects of occult spinal dysraphism

Abstract: Object Neurenteric cysts are infrequently reported congenital abnormalities believed to be derived from an abnormal connection between the primitive endoderm and ectoderm. The authors report a series of 13 patients treated over a 50-year period. Methods Of the 13 patients, seven were female and six were male. Their ages at presentation ranged widely from 5 weeks to 52 years of age. Children presented mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 48 publications
(27 reference statements)
1
47
0
2
Order By: Relevance
“…Rauzzino, et al reported a series of 13 cases of neurenteric cysts. [27] The cysts were most commonly located dorsal to the cord in the thoracolumbar region. Also, neurenteric cyst was associated with another form of OSD in 69% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Rauzzino, et al reported a series of 13 cases of neurenteric cysts. [27] The cysts were most commonly located dorsal to the cord in the thoracolumbar region. Also, neurenteric cyst was associated with another form of OSD in 69% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…4). Neurenteric cysts are relatively benign slow-growing lesions with a recurrence rate of 27% in one series (Rauzzino et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These rare lesions are ectopias in that they are displaced nests of endodermally derived tissue. Historically, neurenteric cysts have been described as enterogenous cysts, enteric cysts, gastrocytomas, dorsal enteric cysts, split notochord cysts, and teratoid cysts (Rauzzino et al, 2001). Neurenteric cysts are often seen in conjunction with other forms of occult spinal dysraphism.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Another theory attribute this discrepancy to the varied positions of Hensen's node (accessory neurenteric canal). [3] A recent theory suggests a primary notochord defect resulting in secondary changes to the paraxial mesoderm, which is responsible for the formation of the spinal column, giving rise to a medial interosseous space. Through this space, the endoderm and the underlying primitive intestine herniate, adhere to the dorsal ectoderm, and eventually rupture.…”
Section: Dear Sirmentioning
confidence: 99%